Pengembangan Sistem Kuis Alogoritma Pemprograman Berbasis Web - Melinda Azizah; Yahfizham Yahfizham (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Online learning offers several advantages, such as lower costs, flexible time, and each participant can adapt to their own learning abilities and developments. With this algorithm, the order of the questions is always different between each participant and when the participant repeats the test. Participants who pass the exam can then take the material to a new level. The purpose of this paper is to design and develop a web-based programming algorithm quiz system and determine the validity of the web-based programming algorithm quiz system. From student observations, facts were found that showed there were obstacles in understanding computer programming problems. Information is obtained by distributing questionnaires to students. From this information, information is obtained that algorithms are the most important programming material. The research results show that the functionality of the media expert assessment programming algorithm quiz system obtained a score of 85.71% for data use, 85% for design, and 85% for functionality. The average data collection was 85.29%. From the research results it can be concluded that the programming algorithm quiz system developed is suitable for use in small corrections.